Redescription of the Himalayan Trachelas costatus (Araneae: Trachelidae) - Marusik, Yuri M.; Omelko, Mikhail M.; Koponen, Seppo (Zootaxa, 2018)
O. Pickard-Cambridge (1885) described Trachelas costata based on female specimens from two localities in the Himalayas. Since then it was only mentioned in two works by Simon (1897, 1906). The World Spider Catalog (2018) indicates its distribution as "China (Yarkand)". All of the species described by O. Pickard-Cambridge (1885), based on material collected during the Second Yarkand Mission, are stored in the Oxford University Museum of Natural History. Vials with material described in this paper contain no species and locality labels (Prószyński & Żochowska 1981; Marusik 1993). It was not difficult to recognize the syntypes of this species due to the figures given by O. Pickard-Cambridge, and also because it is the only trachelid described from Yarkand to date. The goals of our paper are to redescribe Trachelas costatus in detail, designate a lectotype, and comment on its distribution and relationships.